Deletion of Ck2β gene causes germ cell development arrest and azoospermia in male mice - Liang, Qiu‐Xia (Cell Prolif, 2019)
OBJECTIVES: In humans, non‐obstructive azoospermia (NOA) is a major cause of male infertility. However, the aetiology of NOA is largely unknown. Previous studies reported that protein CK2β was abundantly and broadly expressed in spermatogenic cells. Here, we investigate whether protein CK2β participates in spermatogenesis. MATERIALS AND METHODS: In this study, we separated spermatogenic cells using STA‐PUT velocity sedimentation, analysed the expression pattern of protein CK2β by immunoblotting, specifically deleted Ck2β gene in early‐stage spermatogenic cells by crossing Ck2β(fl) mice with Stra8‐Cre(+) mice and validated the knockout efficiency by quantitative RT‐PCR and immunoblotting. The phenotypes of Ck2β(fl/Δ);SCre(+) mice were studied by immunohistochemistry and immunofluorescence. The molecular mechanisms of male germ cell development arrest were elucidated by immunoblotting and TUNEL assay. RESULTS: Ablation of Ck2β gene triggered excessive germ cell apoptosis, germ cell development arrest, azoospermia and male infertility. Inactivation of Ck2β gene caused distinctly reduced expression of Ck2α′ gene and CK2α′ protein. CONCLUSIONS: Ck2β is a vital gene for germ cell survival and male fertility in mice.